Malaysia-Japan Collaboration Strategy for Defence Manufacturing: A Conceptual Study Based on the RBV Theory - Chinnasamy N.A. MALARVIZHI; Shamima R. MANZOOR; Sreenivasan JAYASHREE (Communications of International Proceedings, 2021)
Defence spending is a significant item of public expenditure in most countries and the financing of defence is a major topic of academic and political debate. Initiatives are necessary to enhance the collaboration in transnational defence manufacturing industries through alliance formation that can make important contributions to strengthen the security base of the involved countries for their national and regional levels. This study intends to discuss the defence manufacturing capabilities framework for alliance formation between Malaysia and Japan in light of the Resource Based View (RBV) theory. The discussions have highlighted the internal and external conditions of the relevant companies in both countries with regard to human capital resources, firm-specific resources, and resources embedded in inter-firm relationships that impact the said alliance’s sustainability. This study has analysed the guidelines related to the operationalisation and implementation of the theoretical concepts and ideas of RBV for defence manufacturing companies. The outcomes of this research are expected to provide meaningful insights for the managers in the defence sector for successful transnational collaboration.
Keywords: Alliance in Defence Manufacturing; Japan; Malaysia; Resource-Based View